Calculating Properties of Mode for Step-Index Single-Mode Optical Fibers at 1064 nm Wavelength - Kadhim , Ali A.; Salih , Aqeel R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
The development in the field of technology has led to an increased need to develop optical fibers due to their ability to transmit information and data with the least amount of attenuation over long distances between city centers. In this research, mode properties calculation for five step-index single-mode optical fibers with core radii of (1.9 - 2.9) μm where the increase in radius is 0.25μm, with core and cladding indices (n1=1.4652, n2=1.458496157), respectively and a numerical aperture of 0.14 has been done at 1064 nm wavelength using RP Fiber Calculator (free version 2025). The fundamental fiber mode properties such as effective area, power propagated in the core, propagation constant and effective refractive index were calculated. Intensity distributions for the mode were shown. It was noted that the effect of increasing the core radius led to an increase in the core power and it was also observed that the propagation constant and effective refractive index increase with the increase in the radius of the core. It was obtaining percentage power more than 50%. Results of this work will be useful in the design of optical fibers. Results from the calculator were compared with those calculated from equations and with previous study and it was concluded that all calculated properties are in good agreement